APLIKASI SISTEM PERENCANAAN DAN PEMBANGUNAN DAERAH BERBASIS WEB SERVICE (Studi Kasus : BAPPPEDA Provinsi Gorontalo) - , RAHMAN TAKDIR; , Dr. Ahmad Ashari, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The fact that BAPPEDA Province of Gorontalo did not integrate with existing plan application to another works unit and could not provided regional plan application to another organization. In these researches will be analysing and designing systems of regional planning arrangement. The methods are consisted of literature studying with the relevant concept of web service, collecting data of Bappeda Province Gorontalo plannings. Then it will be implemented with many programming languages, many DBMS, and different operating systems. Results of these researches are applications of government plan using web service as a tool of data communication. This is not using the different platforms of operating systems, programming languages and DBMS as a treatment of integrated applications.